Wholesale Pricing with Asymmetric Information about a Private Label - Johannes Paha (The Journal of Industrial Economics, 2023)
A monopolistic manufacturer produces a branded good that is sold to final consumers by a monopolistic retailer who also sells a private label. The costs of the private label are unobserved by the manufacturer, which affects the terms of the contract offered by the manufacturer to the retailer. Given the revelation principle, the manufacturer distorts the quantity of the branded product downwards to learn those costs. The manufacturer can further reduce the retailer's information rent by distorting the quantity of the private label upwards—but this quantity is typically beyond its control. The optimum can nonetheless be achieved when combining a quantity discount with an end-of-year repayment.
Keywords: 330